2008
DOI: 10.1128/iai.01495-07
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Vaccination with Attenuated Salmonella enterica Serovar Choleraesuis C500 Expressing Recombinant Filamentous Hemagglutinin and Pertactin Antigens Protects Mice against Fatal Infections with both S. enterica Serovar Choleraesuis and Bordetella bronchiseptica

Abstract: Salmonella enterica serovar Choleraesuis strain C500 is a live, attenuated vaccine that has been used in China for over 40 years to prevent piglet paratyphoid. We compared the protective efficacies of subcutaneous (s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 29 publications
4
39
1
Order By: Relevance
“…Niess and Sundquist have shown that, after oral vaccination, these attenuated bacteria could introduce the target DNA into the internal organs and lymph tissues, such as Peyers' patches, mesenteric lymph nodes, spleen, and liver . This strategy of bacterially delivered immunization has proven successful in inducing significant protection against infections . However, in our study, no evidence of integration after immunized inhibin vaccine was shown in any of investigated organs, suggesting the safety of this vaccine.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Niess and Sundquist have shown that, after oral vaccination, these attenuated bacteria could introduce the target DNA into the internal organs and lymph tissues, such as Peyers' patches, mesenteric lymph nodes, spleen, and liver . This strategy of bacterially delivered immunization has proven successful in inducing significant protection against infections . However, in our study, no evidence of integration after immunized inhibin vaccine was shown in any of investigated organs, suggesting the safety of this vaccine.…”
Section: Discussioncontrasting
confidence: 50%
“…Our previous studies have demonstrated that the attenuated crp À /asd À S. choleraesuis C500 strain could be utilized as a delivery system for foreign antigens by using the asd À balanced lethal host vector system [19]. The present study indicated that pVAX-asd-IS vector, containing recombinant inhibin a-subunit (1-32) fragment, could be used as potent enhancer of immunogenicity in mice.…”
Section: Discussionmentioning
confidence: 58%
“…However, we had reason to believe that the ⌬asd mutant would be more effective than previous live attenuated strains. It has been shown that a more protective immune response can be achieved by increasing short-term vaccine persistence, which we attempted with the booster vaccine (5,23,45). Unfortunately, while vaccination with the ⌬asd mutant did indeed protect against acute melioidosis, the vaccine failed to protect against chronic melioidosis.…”
Section: Fig 6 (A)mentioning
confidence: 99%
“…One explanation to the higher IgG response after sc vaccination may be that bacteria trapped in skin are available to trigger the immune system, whereas part of bacteria via ig is killed by acidity in the stomach, or fail to bind PP and are washed away in feces. Similarly, Zhao and co-workers recently reported that the sc route provided higher protection than the oral route for mice vaccination with a live Salmonella vector producing Salmonella or Bordetella antigens [15].…”
Section: Resultsmentioning
confidence: 96%